2019
DOI: 10.1002/ab.21874
|View full text |Cite
|
Sign up to set email alerts
|

Investigating honesty‐humility and impulsivity as predictors of aggression in children and youth

Abstract: Among adult and adolescent populations, the personality trait of honesty-humility (HH) has been linked to aggression. For example, adults low in HH have been found to exhibit higher levels of workplace delinquency and revenge motivation, and adolescent low in HH are more likely to bully others. However, there is a paucity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…We found robust evidence for Hypothesis 1 that Honesty-Humility negatively predicted adolescents' unethical behavior. A growing body of research has found that adolescents low in Honesty-Humility are more likely to engage in antisocial behavior, bullying, and aggressive behavior (Allgaier et al, 2015;MacDonell & Willoughby, 2020;Volk et al, 2018). Our indings extended previous studies by showing that personality trait (i.e., Honesty-Humility) in mid-adolescence is an important predictor of unethical behavior including cheating, lying, and stealing, which provides a better understanding of adolescents' Honesty-Humility on their social behavior.…”
Section: Honesty-humility and Unethical Behaviorsupporting
confidence: 80%
See 2 more Smart Citations
“…We found robust evidence for Hypothesis 1 that Honesty-Humility negatively predicted adolescents' unethical behavior. A growing body of research has found that adolescents low in Honesty-Humility are more likely to engage in antisocial behavior, bullying, and aggressive behavior (Allgaier et al, 2015;MacDonell & Willoughby, 2020;Volk et al, 2018). Our indings extended previous studies by showing that personality trait (i.e., Honesty-Humility) in mid-adolescence is an important predictor of unethical behavior including cheating, lying, and stealing, which provides a better understanding of adolescents' Honesty-Humility on their social behavior.…”
Section: Honesty-humility and Unethical Behaviorsupporting
confidence: 80%
“…A growing body of research suggests that Honesty-Humility plays an important role in explaining unethical behavior in primarily adult populations (Hilbig & Zettler, 2015;Kleinlogel, Dietz, & Antonakis, 2018). Given that recent studies exploring the relationship between adolescents' Honesty-Humility and their unethical behavior were mostly conducted in Canada and Europe (e.g., Allgaier, Zettler, Wagner, Püttmann, & Trautwein, 2015;MacDonell & Willoughby, 2020), the current study intends to explore the role of Honesty-Humility in explaining unethical behavior in Chinese adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 More importantly, if aggressive behaviours become prevalent during this developmental stage, they can be escalated and persist. 8 Evidence from longitudinal research has demonstrated that adolescents with higher aggression levels are at greater risk of criminal activity and violence, peer victimisation, rule-breaking behaviours, internalising symptoms, and narcissistic and borderline personality features in the future. 9 10 Furthermore, adolescents with higher aggressiveness tend to have difficulties in controlling waves of anger in adulthood and have consistently poorer outcomes across life success domains.…”
Section: Introductionmentioning
confidence: 99%
“…21 The changes, stresses and disparities could arouse anger easily. 8 According to Blum et al's framework, 24 adolescence is also a dynamic developmental period of learning and adaptation, which creates both vulnerabilities and unique opportunities for early intervention and prevention. Thus, the identification of risk factors is critical to the understanding of aggressive behaviours among adolescents.…”
Section: Introductionmentioning
confidence: 99%